1972
DOI: 10.1055/s-0038-1649350
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Phylogenetic Canalisation of the Circulating Platelet Mass in Man

Abstract: SummaryPhylogenetically mammalian platelets are an apocrine secretion from nucleated thrombocytes, and biologically the number of circulating fragments is irrelevant compared with their total mass and biochemical function. The literature on human genetic derangements affecting the circulating platelet mass is reviewed. The product of platelet count and platelet volume is shown to be “canalised” since many congenital forms of thrombocytopenia are associated with a reciprocal increase in the mean platelet volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…The low platelet numbers seen in patients with the gray platelet syndromne suggests either that these platelets are being destroyed more readily than normal platelets in the circulation or that megakaryocyte production is decreasecd. Alternatively, there may be an abnormality in separationi of platelets from inegakaryocytes similar to MIediterranean macrothrombocytosis with decreased numbers of large platelets representing a normiial platelet mass (48).…”
Section: Methodsmentioning
confidence: 99%
“…The low platelet numbers seen in patients with the gray platelet syndromne suggests either that these platelets are being destroyed more readily than normal platelets in the circulation or that megakaryocyte production is decreasecd. Alternatively, there may be an abnormality in separationi of platelets from inegakaryocytes similar to MIediterranean macrothrombocytosis with decreased numbers of large platelets representing a normiial platelet mass (48).…”
Section: Methodsmentioning
confidence: 99%
“…Giant platelets have already been observed within the megakary ocytes [6][7][8]. The total peripheral platelet mass is regarded to be normal [1,5]. Therefore, it was postulated that the underlying defect of this dis ease is a disturbance of megakaryocyte maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Since his mean platelet volume was increased (11.1 µm 3 ), the thrombocytopenia was probably relative, as it is in other giant platelet syndromes, and the circulating platelet biomass (platelet number × mean platelet volume) was normal. 78 Aggregation studies revealed an essentially normal response to most aggregating agents. However, the reaction of gray platelets to collagen and thrombin was less than normal.…”
Section: Alpha Granulesmentioning
confidence: 98%
“…78 Erythrocyte stomatocytosis is also observed in high frequency in the population. Individuals with this problem do not have a bleeding tendency.…”
Section: Mediterranean Macrothrombocytopeniamentioning
confidence: 99%
See 1 more Smart Citation